Best Answer

There is no answer - it is an error: negative numbers do not have logarithms.

The log if a number tells to what power the (positive) base must be raised to get the number. Raising any positive number to any power will never result in a negative number, so it is an error to try and take the log of a negative number.

🙏

🤨

😮

Q: Log -3 equals

Write your answer...

Submit

Related questions

If the log of x equals -3 then x = 10-3 or 0.001or 1/1000.

0.4772

x = 3*log8 = log(83) = log(512) = 2.7093 (approx)

log(-3,2.3914850069628266…i) = 1.26ie. (-3)1÷1.26=2.3914850069628266…i

log(x) = 3x = 10log(x) = 103 = 1,000

3^(-2x + 2) = 81? log(3^(-2x + 2)) = log(81) (-2x+2)log(3) = log(81) -2x = log(81)/log(3) - 2 x = (-1/2)(log(81)/log(3)) + 1

3x = 18Take the logarithm of each side:x log(3) = log(18)Divide each side by log(3):x = log(18) / log(3) = 1.25527 / 0.47712x = 2.63093 (rounded)

log 3 is a constant, so d/dx log3, like d/dx of any constant, equals zero.

8.865433979891739 raised to the power of ten equals 3 billion (3,000,000,000).x^10 = 3x10^9log x * 10 = 0.477 + 9log x * 10 = 9.477log x =0.9477x = 8.865433979891739

log3 + logx=4 log(3x)=4 3x=10^4 x=10,000/3

[log2 (x - 3)](log2 5) = 2log2 10 log2 (x - 3) = 2log2 10/log2 5 log2 (x - 3) = 2(log 10/log 2)/(log5/log 2) log2 (x - 3) = 2(log 10/log 5) log2 (x - 3) = 2(1/log 5) log2 (x - 3) = 2/log 5 x - 3 = 22/log x = 3 + 22/log 5

log(9x) + log(x) = 4log(10)log(9) + log(x) + log(x) = 4log(10)2log(x) = 4log(10) - log(9)log(x2) = log(104) - log(9)log(x2) = log(104/9)x2 = 104/9x = 102/3x = 33 and 1/3

Use the identity log(ab) = log a + log b to combine the logarithms on the left side into a single term. Then take antilogarithms (just take the log away) on both sides.

-Log(1.4x10-3)= 2.85 The Log to be used here is the decimal one, not the neperian one.

It's a logarithmic equation in one unknown.If you'd like to know the value of 'x' that makes it true, you can find it like this:15 log(2.5x) = 100log(2.5x) = 100/15 = 20/3log(2.5) + log(x) = 20/30.39794 + log(x) = 20/3log(x) = 20/3 - 0.39794x = 1020/3 / 100.39794x = 1,856,635.533=============================Check:log(2.5 x 1,856,635.533) = 20/315 (20/3) = 300/3 = 100 yay!

- log(0.00097) = 3 pH ------------

log3(x)=4 x=3^4 x=81

2 log(x) + 3 log(x) = 105 log(x) = 10log(x) = 10/5 = 210log(x) = (10)2x = 100

Log4 64=y 64=4y 26=22y Therefore y=3

2 log(4y) = log7(343) - log5(25)log7(343) = 3log5(25) = 22 log(4y) = 3 - 2 = 1log(4y) = 0.54y = sqrt(10)y = 0.25 sqrt(10)y = 0.79057 (rounded)

Without brackets, there are many ambiguities in the question. 4 = 2/3*log(x) - 0.9 4.9*3/2 = logx 7.35 = logx so x = 107.35 However, the original equation could also have referred to 4 = 2/3*log(x-0.9) or 4 = 2/[3*log(x)] - 0.9 or 4 = 2/[3*log(x-0.9)]

log(36) = 1.5563To solve this problem without using a scientific calculator, factor 36 into 2*2*3*3, and use the formula:log(a*b) = log(a) + log(b)So, in this case:log(36) = log(2) + log(2) + log(3) + log(3) = 0.3010 + 0.3010 + 0.4772 + 0.4772 = 1.5564 (slight rounding error)

1

Original Statement:x - 1 + 2 + log(x) = 3Simplify:x + 1 + log(x) = 3Subtract 1:x + log(x) = 2Lambert W-Function:x = (W(100*ln(10))/(ln(10)) = 1.7555794993... (rounded up).This considered log(x) to be base 10 log (x).

log (3 x 66) = log 3 + log 66